An analysis of 2800 CT Head scans in patients with chronic headache - Rekha Khare; A.K. Khare (International Journal of Medical Research and Review, 2019)
Introduction: Chronic headache is a common health problem in general medical practice and there is increasing demand of CT scan from specialist as well as non-specialist doctors to refer patients for CT head scan.Patients and methods: The present study was done on 2800 CT head scans of patients with problem of chronic headache. While patients in Group 1 (n=1900) had only chronic headache without any neurological findings, Group B comprised of cases (n=900) referred by specialist doctors after neurological examination. CT scan was done by trained technicians and contrast was injected where necessary.Results: Present study showed majority of patients in both group 1 and group 2 (90% and 87.7% respectively) had normal CT findings or insignificant findings. However, difference was not significant in both groups when significant findings (10.0% Gr. A and 12.2% Group B) were compared.Discussion: Our findings are consistent with other studies concluding that routine CT scan may not provide clinically useful information in chronic headache.